Investigating Students’ Learning Environment in English Speaking for Senior High School - Hafiz, Hairori Sahrul; Sakrani, Ahmad; Kertawijaya, Lalu (Humanitatis : Journal of Language and Literature, 2025)
The importance of mastering English speaking skills and the influence of the learning environment are the main targets for students. The problems that may exist among senior high school students include a lack of speaking practice, discomfort in public speaking, and pressure from the surrounding environment that hinders the learning process. This study aims to explore and analyze how the learning environment affects students’ ability to speak English. This study employs a descriptive quantitative method in which the data are collected through observation, interviews, and documentation. Observation is conducted by distributing questionnaires to 26 eleventh-grade students, and interviews are then carried out to explore more in-depth information about students’ experiences, perceptions, and views on the learning environment. The data are statistically analyzed to identify trends, student perceptions, and dominant factors that support or hinder English speaking within the learning environment. The findings show that most students perceive the learning environment as quite supportive in terms of facilities, teacher support, student involvement, peer support, classroom atmosphere, and speaking practice. However, challenges such as a lack of confidence and the limited use of English outside the classroom remain significant obstacles. The learning environment plays an important role in supporting students’ confidence, along with positive teacher support through the use of collaborative learning strategies, presentations, and technology. Additionally, student involvement is categorized as a high indicator of a participatory atmosphere. Facilities, however, remain an aspect that needs to be improved to encourage more active communication. Peer support is also a challenge, as some students feel less supported during group work. Meanwhile, teachers have managed to provide many opportunities for students to speak, which encourages them to become more active and orally skillful. These findings are expected to provide valuable input for schools in creating a more effective learning environment that enhances students’ English-speaking abilities.